Improving passing skills on volleyball using target games approach - Khurotul Aini (UIR Press, 2021)
Passing on volleyball is important in volleyball games, but students have difficulty determining the exact passing result with the target. This study improves the passing skills on volleyball in volleyball learning on students of VII A grade in-state junior high school 1 Probolinggo using the target games approach. The research method uses Classroom Action Research. The implementation of this class action is by two cycles. Each cycle consists of 4 stages, namely (1) planning, (2) implementation, (3) observation, and 4) reflection. The subjects of this study are students of VII A grade in State Junior High School 1 Probolinggo. The collecting techniques of the data use observation sheets, documentation, and tests. The results of the passing skills test on volleyball in the first cycle, the number of students amount 30 people, there are 29 students able to do the passing beginning movement on the volleyball correctly 90.25% with good category, 27 students can do the movements correctly in the subject position of 81.12 % with good category, and 28 students are able to make the final movement correctly 80.25% with a good category. Based on the results of the study, it can be concluded that learning of passing on volleyball through the target games approach can improve the passing skills on volleyball of students in State Junior High School Probolinggo. It is hoped that in the future, research can be found that develops target games with other types of games to overcome student learning difficulties.